E-Module IPA Bermuatan Etnovlog Pantai Lon Malang Madura: Bahan Ajar untuk Meningkatkan Literasi Sains Siswa - Rizqoh Mufidah; Nur Qomaria; Aditya Rakhmawan; Eva Wahyuni; Dwi Putera (PT. Komunitas Peneliti Alinea, 2025)
The e-module containing the Lon Malang beach ethnovlog is one of the digital teaching materials integrated with local wisdom. This research is important to do because it aims to determine the validity of the e-module product containing the Lon Malang beach ethnolog and increase students' scientific literacy on the material of Indonesian ecology and biodiversity. This type of research is research and development (R&D). The development of this media uses the ADDIE learning model (analyze, design, development, implementation, evaluation). The research was conducted at SMPN 1 Sreseh in the even semester of the 2024/2025 academic year. Data collection used questionnaires, tests, interviews, observation and documentation techniques. The results of the study show that: (1) The developed e-module is very valid with a media aspect score of 93.52% while the material aspect is 89.24%, (2) The e-module containing the Lon Malang beach ethnolog can increase students' scientific literacy with an N-gain value of 0.65 in the moderate category. Thus, students' scientific literacy skills can be measured and improved with teaching materials in the form of e-modules that have been developed.